The Cross-Sectional Distribution of Price Stickiness Implied by Aggregate Data - Carvalho, Carlos; Dam, Niels Arne; Lee, Jae Won (The Review of Economics and Statistics, 2020)
We provide evidence on three mechanisms that can reconcile frequent individual price changes with sluggish aggregate price dynamics. To that end, we estimate a semistructural model that can extract information about real rigidities and the distribution of price stickiness from aggregate data. Hence, the model can also speak to the debate about the aggregate implications of sales. Our estimates indicate large real rigidities and substantial heterogeneity in price stickiness. Moreover, the cross-sectional distribution of price stickiness implied by aggregate data is in line with an empirical distribution obtained from microprice data that factors out sales and product substitutions.